Brangelina - Halperin, Ian (Montreal, Quebec : Transit Publishing, 2009)
The superstar couple Brad Pitt and Angelina Jolie and their Hollywood spin-machine handlers have successfully manipulated the public into believing a glamorous fairytale that bears little resemblance to the reality of the pair's life together.
Brangelina
Keywords: Jolie, Angelina, -- 1975-; Pitt, Brad, -- 1963-; Actors -- United States -- Biography